Contesting human remains in museum collections : the crisis of cultural authority - Jenkins, Tiffany. (Routledge research in museum studies ;, 2011)
An examination of the construction of contestation over human remains from a sociological perspective, this work advances an emerging area of academic research, setting the terms of debate, synthesizing disparate ideas, & making sense of a broader cultural focus on dead bodies in the contemporary period.